Open Access Publishing in Canada: Current and Future Library and University Press Supports - Taylor, Donald; Morrison, Heather; Owen, Brian; Vézina, Kumiko; Waller, Andrew (Université d'Ottawa | University of Ottawa, 2013)
Canadian university libraries, Canadian university presses, and non-university scholarly presses at Canadian universities were surveyed in the first part of 2010 as to the level of their support of Open Access (OA) journal publishing. Respondents were asked about journal hosting services in their organization as well as their thoughts on internal and external support for open access publishing. Results showed that most of the organizations are hosting OA journals, largely between one and five in number, and many supply journal hosting services, including some technical support. Personnel resources are a notable factor in the ability to host journals. Most respondents engage in some sort of internal support for open access publishing and are open to options that they are presently not utilizing. They are particularly amenable to OA publishing support from outside of their organizations, especially assistance at a consortial level.
Keywords: open access; open access publishing; scholarly communication; academic libraries; universities; Canada; university presses